Stock Assessment Using the LBB Method for Portunus trituberculatus Collected from the Yangtze Estuary in China - Longtao Yue; Yibang Wang; Hui Zhang; Weiwei Xian (Applied Sciences, 2020)
Portunus trituberculatus is an important invertebrate species distributed in the Yangtze Estuary. However, its biomass and enrichment have been affected seriously by ongoing human activity in recent decades. The length-based Bayesian biomass estimator (LBB) is a novel and potent method to estimate the stocks for most commercial fishes and invertebrates in offshore using only length and frequency data. In this study, the results showed that the ratio of current exploited biomass relative to unexploited biomass (B/B0) was smaller than relative biomass capable of producing maximum sustainable yields (BMSY/B0) after handling of the catches of the P. trituberculatus collected from the Yangtze Estuary in 2018 using the LBB method. Therefore, this evidence indicated that the biomass of the swimming crab was relatively low as a result of the overfishing in this water area and the catches of the crabs should be controlled at a reasonable level in the future. Meanwhile, LBB is a promising method providing a theoretical basis for the management and protection of fishery resources.